2022
DOI: 10.1177/09544089221080820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extrusion parameters on drilling machinability of AZ31 magnesium alloy

Abstract: AZ31 magnesium alloy is mainly used in aerospace applications due to its lightweight and good mechanical properties. The installation of AZ31 alloy in an aircraft usually requires machining operations such as drilling and milling for assembly purposes. The current study aims to investigate the effects of different extrusion ratios (1.77, 2.68, 3.55) on the drilling machinability of AZ31 alloys. The machinability was evaluated with thrust force, borehole surface quality, and chip characteristics. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…CFRP, aluminum alloys, and magnesium alloys have been used in vehicle bodies to achieve lightweight due to their high specific strength. [2][3][4] These lightweight materials promote the realization of multimaterial hybrid car bodies, but they also pose challenges to the joining processes between dissimilar sheets.…”
Section: Introductionmentioning
confidence: 99%
“…CFRP, aluminum alloys, and magnesium alloys have been used in vehicle bodies to achieve lightweight due to their high specific strength. [2][3][4] These lightweight materials promote the realization of multimaterial hybrid car bodies, but they also pose challenges to the joining processes between dissimilar sheets.…”
Section: Introductionmentioning
confidence: 99%
“…These state-of-the-art techniques can be used to enhance the mechanical properties of low-ductility and high-utility alloys like the magnesium and titanium alloys [ 13 ], most notably those having rare earth alloying elements. Various extrusion ratios have been tested on Mg-AZ31 alloy, so as to demonstrate its machinability properties in terms of milling and drilling operations [ 14 ]. To produce materials with evenly distributed arrays of ultrafine grains and better mechanical characteristics, including extraordinary superplastic capabilities, SPD methods were therefore introduced for the manufacturing of magnesium alloys.…”
Section: Background and Introductionmentioning
confidence: 99%
“…In the literature [14], after adding different contents of Bi to Mg alloy, it was found that the addition of Bi prolongs the aging process of the alloy and also effectively suppresses the appearance of discontinuous precipitation. Also, the addition of Bi resulted in the precipitation of a continuous precipitation phase, which is a complex semi-coherent lattice phase relationship between the phase and the matrix, improving the mechanical properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%